2017
DOI: 10.3748/wjg.v23.i3.426
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and effects of oestrogen in rat gastric mucosal defence

Abstract: AIMTo evaluate sex differences and the effects of oestrogen administration in rat gastric mucosal defence.METHODSSex differences in gastric mucus thickness and accumulation rate, absolute gastric mucosal blood flow using microspheres, the integrity of the gastric mucosal epithelium in response to a chemical irritant and the effects of oestrogen administration on relative gastric mucosal blood flow in an acute setting was assessed in an in vivo rat experimental model. Subsequently, sex differences in the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Additionally, the levels and modes of secretion of hormones differ between males and females, therefore, hormones are also thought to play a role in the differences observed between sexes (Li et al, 2013 ). A recent study showed that gastric mucosal blood flow is higher in male than in female rats, and is reduced in male rats by estrogen administration (Shore et al, 2017 ), which lead us to consider whether hormones are involved in the regulation of the disposition of CK. Nevertheless, additional mechanisms could simultaneously be involved, with different effects on blood concentrations of the parent drug and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the levels and modes of secretion of hormones differ between males and females, therefore, hormones are also thought to play a role in the differences observed between sexes (Li et al, 2013 ). A recent study showed that gastric mucosal blood flow is higher in male than in female rats, and is reduced in male rats by estrogen administration (Shore et al, 2017 ), which lead us to consider whether hormones are involved in the regulation of the disposition of CK. Nevertheless, additional mechanisms could simultaneously be involved, with different effects on blood concentrations of the parent drug and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be due to the differences in male and female rat physiology; previous research has shown that oestrogens are inhibitors of the gastric acid secretion whilst testosterone is an inducer [11,12]. However, in a recent study, it was found that males have a higher gastric blood flow than their female counterparts [13]. Oestrogen administration was able to reduce the mean blood flow in the gastric mucosa by 31%…”
Section: Gastrointestinal Fluid Phmentioning
confidence: 95%
“…Overall, no significant sex differences were identified in the pH profile expect for a lower pH in the fundus and antrum in female rats when compared to males (Figure 1). In a recent study, it was found that male rats have a higher gastric blood flow than their female counterparts [29]. Oestrogen administration was found to reduce the mean blood flow in the gastric mucosa by 31% in males; however, it remained largely unchanged in females.…”
Section: Luminal Fluid Characterisationmentioning
confidence: 95%